2017
DOI: 10.3389/fmicb.2017.01212
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Acquisition and the Metabolic Potential of Photoferrotrophic Chlorobi

Abstract: Anoxygenic photosynthesis evolved prior to oxygenic photosynthesis and harnessed energy from sunlight to support biomass production on the early Earth. Models that consider the availability of electron donors predict that anoxygenic photosynthesis using Fe(II), known as photoferrotrophy, would have supported most global primary production before the proliferation of oxygenic phototrophs at approximately 2.3 billion years ago. These photoferrotrophs have also been implicated in the deposition of banded iron for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 100 publications
1
24
0
1
Order By: Relevance
“…The RDA analysis agreed with the fact that many species belonged to Cyanobacteria and Chlorobi are capable of nitrogen fixation to support primary production [49,50]. The high composition of Cyanobacteria and Chlorobi in the FFD pond suggested that the nitrogen removal was mainly performed through nitrogen fixation.…”
Section: Correlations Between Water Quality and Microbial Communitysupporting
confidence: 74%
“…The RDA analysis agreed with the fact that many species belonged to Cyanobacteria and Chlorobi are capable of nitrogen fixation to support primary production [49,50]. The high composition of Cyanobacteria and Chlorobi in the FFD pond suggested that the nitrogen removal was mainly performed through nitrogen fixation.…”
Section: Correlations Between Water Quality and Microbial Communitysupporting
confidence: 74%
“…All isolated photoferrotrophs from the green sulfur bacteria belong to the genus Chlorobium. These include Chlorobium ferrooxidans strain KoFox (Heising et al, 1999) and two recently isolated species: Chlorobium phaeoferrooxidans Thompson et al, 2017) and Chlorobium sp. strain N1 which is closely related to Chlorobium luteolum (Laufer et al, 2017).…”
Section: Physiology Existing Isolates/cultures and Ecologymentioning
confidence: 99%
“…It is believed that before reduced sulfur compounds accumulated, ferrous ion (Fe 2+ ) was used as electron donor. For example, ferrous ion functions as the electron source in type 1 photosystem in some green sulfur bacteria, also known as Chlorobi, such as Chlorobium ferrooxidans , as well as in type 2 photosystem found in some purple nonsulfur bacteria . There is some evidence that biological Fe 2+ oxidation took place approximately 3.77 Ga ago , but whether it was by photooxidation is still unknown.…”
Section: Photosystemsmentioning
confidence: 99%